Unveiling the Blockchain Intention-Behavior Gap Among Young Developers - Suwarno, Suwarno; Yoprisyanto, Josua; Aklani, Syaeful Anas (Politeknik Negeri Batam, 2026)
This study assesses the factors influencing blockchain technology acceptance among young developers in Batam, Indonesia, with a specific focus on comparing two distinct behaviors: using blockchain-based applications and engaging in blockchain development. Data were collected through a survey of 215 young developers and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The main outcomes reveal two fundamentally different adoption pathways. The intention to use blockchain applications is primarily driven by personal engagement and social influence, reflecting a